Multilevel analysis of late antenatal care booking and its predictors among pregnant women in extremely high and very high maternal mortality sub-Saharan African countries: evidence from recent demographic and health surveys data - Tesfahun Zemene Tafere; Kaleb Assegid Demissie; Getachew Teshale; Misganaw Guadie Tiruneh; Endalkachew Dellie; Demiss Mulatu Geberu; Asebe Hagos; Nigusu Worku; Melak Jejaw (BMC Pregnancy and Childbirth, 2025)
Abstract Background Late booking of antenatal care is a major contributing factor to the high rate of maternal deaths. Despite the World Health Organization’s recommendation for pregnant women to begin their first antenatal care visit within 12 weeks of gestation, delays in initiating antenatal care are common in sub-Saharan Africa. Therefore, this study intended to examine the prevalence of late antenatal care booking and its predictors in extremely high (over 1,000 maternal deaths per 100,000 live births) and very high (between 500 and 1,000 maternal deaths per 100,000 live births) maternal mortality sub-Saharan African countries. Methods Our analysis utilized secondary data from the most recent Demographic and Health Surveys conducted between 2014 and 2022. A weighted sample of 74,552 women who had given birth within five years preceding the survey and had antenatal care visits for their last child were included. A multilevel mixed-effect logistic regression model was fitted. Statistical significance was declared at a p-value less than 0.05. Results The pooled prevalence of late antenatal care booking in extremely high and very high maternal mortality sub-Saharan African countries was 70.16% (95% CI: 69.83,70.49). Poor wealth quantile (AOR = 1.71, 95%CI: 1.60,1.82), low community media exposure (AOR = 1.70, 95%CI: 1.63,1.78), grand multiparous (AOR = 1.66, 95%CI:1.52,1.81), no media exposure (AOR = 1.59, 95%CI, 1.52,1.67), married (AOR = 1.53, 95%CI: 1.44,1.63), middle wealth quantile (AOR = 1.41, 95%CI: 1.33,1.51), not autonomous of house-hold decision-making (AOR = 1.28, 95%CI: 1.22,1.34), multiparous (AOR = 1.27, 95%CI, 1.18,1.35), secondary education (AOR = 1.24, 95%CI: 1.16,1.34), family size of 5+ (AOR = 1.24, 95%CI:1.15,1.33), rural residence (AOR = 1.22, 95%CI: 1.15,1.30), big problem of distance (AOR = 1.20, 95%CI: 1.14,1.26), Not working (AOR = 1.17, 95%CI: 1.11,1.23), partner’s no formal education (AOR = 1.17, 95%CI:1.08,1.27), age 15–24 years (AOR = 1.16, 95%CI:1.07,1.25), female household head (AOR = 0.85, 95%CI: 0.80,0.91) were significant predictors of late antenatal care booking. Conclusions This study revealed that on average, seven in ten pregnant women in extremely high and very high maternal mortality sub-Saharan African countries booked antenatal care late. Both individual and community-level factors influenced late antenatal care booking. The study recommends empowering women, improving rural healthcare access, and promoting comprehensive ANC education and community-based interventions to address late ANC booking in extremely high and very high maternal mortality SSA countries.